Approaching postmodernism : papers presented at a Workshop on Postmodernism, 21-23 September 1984, University of Utrecht - Workshop on Postmodernism (1984 : University of Utrecht); Fokkema, Douwe Wessel, 1931-2011.; Bertens, Johannes Willem (Amsterdam ; Philadelphia : Benjamins, 1986)
Most of the essays collected in this volume deal with theoretical issues that dominate the international debate on Postmodernism, issues such as the shifting nature of the concept, the problem of periodization and the problem of historicity. Other essays offer readings of Postmodernist texts and relate practical criticism to a theoretical framework. Hans Bertens (Utrecht) sketches the historical development of the concept Postmodernism in American criticism, distinguishing between the various definitions that have been proposed over the last twenty-five years, in an attempt to bring some order.
Postmodernism in Russian Drama: Vampilov, Amalrik, Aksënov; The Absurd and its Forms of Reduction in Postmodern American Fiction; Postmodernism in American Fiction and Art; Modernism Cut in Half: The Exclusion of the Avant-garde and the Debate on Postmodernism; Postmodernism and Some Paradoxes of Periodization; Naming and Difference: Reflections on ""Modernism versus Postmodernism"" in Literature; Note on the Contributors; References; Index; The series Utrecht Publications in General and Comparative Literature
Includes bibliographical references (pages 275-289) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Literature, Modern -- 20th century -- History and criticism -- Congresses; Postmodernism (Literature) -- Congresses; Postmodernism -- Congresses; Postmodernism (Literature) -- Congresses; Littérature -- 20e siècle -- Histoire et critique -- Congrès.; Postmodernisme -- Congrès.; Postmodernisme (Littérature) -- Congrès.; Postmodernisme (Littérature) -- Congrès.; BIOGRAPHY & AUTOBIOGRAPHY -- Literary; Postmodernism; Literature, Modern; Postmodernism (Literature); Literatuurwetenschap; Postmodernisme; 1900-1999; Conference papers and proceedings; Criticism, interpretation, etc